Methanotrophic bacteria in warm geothermal spring sediments identified using stable‐isotope probing. Issue 1 (22nd July 2014) - Sharp, Christine E.; Martínez‐Lorenzo, Azucena; Brady, Allyson L.; Grasby, Stephen E.; Dunfield, Peter F.
Abstract We investigated methanotrophic bacteria in sediments of several warm geothermal springs ranging in temperature from 22 to 45 °C. Methane oxidation was measured at potential rates up to 141 μmol CH4 d−1 g−1 sediment. Active methanotrophs were identified using 13CH4 stable‐isotope probing (SIP) incubations performed at close to in situ temperatures for each site. Quantitative (q) PCR of pmoA genes identified the position of the heavy (13C‐labelled) DNA fractions in density gradients, and 16S rRNA gene pyrotag sequencing of the heavy fractions was performed to identify the active methanotrophs. Methanotroph communities identified in heavy fractions of all samples were predominated by species similar (≥ 95% 16S rRNA gene identities) to previously characterized Gammaproteobacteria and Alphaproteobacteria methanotrophs. Among the five hottest samples (45 °C), members of the Gammaproteobacteria genus Methylocaldum dominated in two cases, while three others were dominated by an OTU closely related (96.8% similarity) to the Alphaproteobacteria genus Methylocapsa. These results suggest that diverse methanotroph groups are adapted to warm environments, including the Methylocapsa‐Methylocella‐Methyloferula group, which has previously only been detected in cooler sites.